Risk factors and mortality of SARS-CoV-2 reinfection during the Omicron era in Taiwan: A nationwide population-based cohort study - Yi-Hsuan Chen; Cheng-Yi Lee; Hao-Yuan Cheng; Chiu-Mei Chen; Yu-Neng Cheuh; Chia-Lin Lee; Hung-Wei Kuo (Journal of Microbiology, Immunology and Infection, 2024)
Background: Prior to 2022, Taiwan had effectively contained the domestic COVID-19 epidemic. However, during 2022, the country encountered multiple large outbreaks of COVID-19, with patients experiencing their first or second infection (reinfection) were both predominantly caused by the Omicron variant. Data are lacking on the risk factors and mortality of COVID-19 reinfection in Omicron era. Methods: In this retrospective population-based cohort study, we recruited COVID-19 patients with their first episode confirmed between April 1, 2022 and June 11, 2022. A reinfection patient was defined as an individual who infected again by SARS-CoV-2 with an interval of more than 90 days. Demographic characteristics, severity of underlying diseases, and vaccination status were adjusted to identify risk factors for reinfection and to further evaluate the hazard of all-cause mortality within 30 days between reinfection and non-reinfection patients. Results: There were 28,588 reinfection patients matched with 142,940 non-reinfection patients included in this study. We found that being female, younger in age, having more severe underlying diseases, and not being fully vaccinated against COVID-19 were risk factors for reinfection. After adjusting for confounding factors, reinfection patients were at a significantly higher risk of all-cause mortality within 30 days (aHR = 4.29, 95% CI: 3.00–6.12, p < 0.001) comparing with non-reinfection patients. Conclusion: During the SARS-CoV-2 Omicron era, reinfection patients were observed to have an increased risk of all-cause mortality. To reduce the disease burden and minimize the risk of reinfection, it is crucial for vulnerable patients to receive full vaccination and adhere to recommended precautions.